Web Engineering Methods in Building aWeb-Based School Academic Information System - Helda, Yudiastuti; Irwansyah, . (INTI International University, 2024)
The advancement of computer technology has paved the way for the development of computer-based information systems, significantly enhancing the efficiency and speed of data processing tasks. In educational settings, particularly in secondary vocational schools, there is a pressing need to transition from traditional manual data handling methods to more sophisticated, automated systems. This study focuses on the development of an academic web application aimed at improving the data processing quality in a secondary vocational school where data is currently managed manually using paper and pen.The existing manual method of processing academic data could be more efficient, prone to errors, and susceptible to data loss. This antiquated approach hinders the school's ability to manage academic information effectively, leading to delays and inaccuracies in data reporting and access. There is a clear necessity for a system that can streamline data processing, ensure data security, and provide easy access to information.The method employed to design this academic information system is web engineering. Web engineering combines engineering principles, management practices, and systematic approaches to create high-quality web-based applications. The development process includes several critical activities: formulation, planning, analysis, engineering, page generation, and testing. The system is implemented using PHP and MySQL, which were chosen for their robustness and reliability in web application development.The development and implementation of the academic information system have demonstrated significant improvements in data processing quality. The system allows for efficient, accurate, and secure handling of academic information. It facilitates quick accessto data from any location, enhancing the practicality of data management. Testing confirmed that all system functions met the predefined requirements, ensuring that the application operates as intended. The introduction of this web-based system has effectively addressed the deficiencies of the previous manual method, providing timely and accurate reporting. This improvement has enhanced the services provided to students, teachers, and principals, leveraging modern technology to achieve greater efficiency in educational administration.